Sifat Kimia dan Mikrobiologi Keju Tomme Probiotik dengan Variasi Perbandingan Kultur Starter Lokal - Buana, Made Justin Satria Wira; Nocianitri, Komang Ayu; Puspawati, Ni Nyoman; Rahayu, Endang Sutriswati (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 13 No 4 (2024): Jurnal ITEPADO - 10.24843/itepa.2024.v13.i04.p02, 2024)
Tomme cheese is a type of semi-hard cheese with characteristics of a yellowish rind, elastic texture, dense structure, earthy aroma, and a dominant salty taste among other flavors. This cheese is suitable to be used as a carrier for probiotics because its according to the tastes of the Indonesian people. However, the use of Streptococcus thermophilus Dad-11 as a pH-lowering bacteria can interfere with the growth of Lactiplantibacillus plantarum subsp. plantarum Dad-13 on tomme cheese. This research aims to determine the effect of starter culture comparisons on the chemical and microbiological properties of tomme cheese and to determine the comparison of starter cultures that are capable of producing the best quality of tomme cheese. A Randomized Complete Block Design (RCBD) were used, with 3 treatments, namely a comparison of L. plantarum subs plantarum Dad-13 and S. thermophilus Dad-11 (1:1), (1:2), and (1:3). The treatment was repeated 3 times, so 9 experimental units were obtained. The obtained data were analyzed by Kruskal Wallis which was followed by Least Significant Difference (LSD) test on SPSS. The research results showed that the comparison of local starter cultures had a significant effect on the reducing the pH, probiotic cell viability, moisture content of lean material, fat content, protein content of tomme cheese. Probiotic tomme cheese with a comparison of L. plantarum subs plantarum Dad-13 and S. thermophilus Dad-11 (1:1) had the best chemical and microbiological characteristics with a decrease in coagulation pH of 5-4-5.5 for 925 minutes (15 hours 25 minutes), final pH of 5.25, viability probiotic cells at the end of aging 10.3 logCFU/g, moisture content of lean material 47.23%, fat content 47.37%, and protein content 43.06%. Keywords: comparison of starters cultur, probiotic tomme cheese, Streptococcus thermophilus Dad-11, and Lactiplantbacillus plantarum subs. plantarum Dad-13.